Pembuatan Minyak Kemenyan (Minyak Obat Tradisional Khas Aceh) dengan Variasi Jenis Bahan Baku Minyak dan Konsentrasi Bahan Pewangi - Normalina Arpi (Jurnal Teknologi dan Industri Pertanian Indonesia, 2013)
“Minyak kemenyan” is one of Aceh’s unique products made from “pliek u” oil that is coconut oil produced traditionally from fermented coconut. Process in making minyak kemenyan is still traditional using main raw material pliek u oil, benzoe, and pleasant smell herbal which resulted in specific scent of minyak kemenyan. The oil is believed by Acehnese can cure some diseases and often use as a medicinal oil.The aim of this research is to study effects of using variety of vegetable oils (pliek u oil, hot extracted copra oil, and palm oil), and scented herbal concentration on the quality of minyak kemenyan. A randomized block design arranged factorially with three replicates was used. Product analysis were acid value, peroxide value, ester value, and sensory evaluation on smell and color of minyak kemenyan.Traditional purifying process of pliek u oil, and copra oil decreased the acid, peroxide, and iodine values of the oils. Whereas scented herbal concentration caused no significant effect on any quality values of minyak kemenyan. Processing the vegetable oils into minyak kemenyan caused slightly increased in the acid and iodine values, but significantly decreased the peroxide value of that made from pliek u oil. The best treatment was minyak kemenyan produced using pliek u oil with acid value of 6.20 mg KOH/g, peroxide value of 18,20 mgO2/100g sampel, iodine value of 4.53 Iod/100 g, ester value of 173.96 mg NaOH/g, smell and color prefered by panelist with scores of 3.0 (=ordinary) and 3.6 (=like), respectively.Keywords: traditional product, “minyak kemenyan”, “pliek u oil”, benzoe, scented herbal